Influence of the season on the metabolic profile in Chios sheep - Igor Dzadzovski; Irena Celeska; Igor Ulchar; Aleksandar Janevski; Danijela Kirovski (Macedonian Veterinary Review, 2015)
Chios is a breed of sheep selected for milk production, with metabolic features typical for a dairy sheep breed. The energy requirements of pregnant sheep is increase in the last weeks of gestation. Metabolic imbalance in the late pregnancy in sheep, usually causea metabolic disorder known as pregnancy toxemia. Additionally, a pregnant sheep exposed to low environmental temperatures has increased energy demands, due to its adaptation to undesirable environmental conditions. The aim of this study was to compare the metabolic profile of Chios sheep exposed to different environmental conditions. Two groups of ewes were instigated. First group included 8 pregnant ewes with clinical signs of pregnancy toxemia exposed to cold stress during the winter season. The second group included 8 non-pregnant, clinically healthy ewes, that were examined during the non-breeding period, in the spring season. Blood samples were taken and serum concentrations of glucose, beta-hydroxybutirate (BHBA), total protein, albumin, urea, creatinine, triglyceride and cholesterol, as well as activity of AST and ALP were determined. Pregnant ewes exposed to cold stress had significantly lower levels of glucose and total protein, and significantly higher levels of BHBA, albumin and AST in the serum compared to non-pregnant ewes that were in optimal environmental conditions. There was no significant difference between the serum levels of urea, creatinine, cholesterol, triglycerides and ALP among the groups. In conclusion, low environmental temperature and poor feeding during the winter season caused metabolic distress in pregnant ewes during the early winter season.